Incidencia de la infección por el virus de la hepatitis A diagnosticadas en la ciudad de Maracaibo, estado Zulia, Venezuela - Costa-León Luciana; Porto-Espinoza Leticia; Monsalve-Castillo Francisca; Callejas-Valero Diana; Estévez Jesús; Castellanos-Sánchez María Elena (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2010)
Abstract: Hepatitis A virus (HAV) infection continues to be a public health problem in developing countries. The aim of this study was to determine incidence of the hepatitis A virus infection in a population from Maracaibo, Venezuela. From January, 2004 until December, 2007, this study was carried out on 1056 individuals, whose ages were between 1-60 years (average ± DS: 27.48 ± 5.24 years), coming from the Maracaibo and San Francisco municipalities, Venezuela. The IgM antibody against HAV was determined by the ELISA technique. The overall incidence was 26.6%. The North, South, East and West areas of the Maracaibo Municipality and the San Francisco Municipality in the city of Maracaibo showed incidences of 73 (35.1%), 76 (28%), 66 (24.3%), 35 (20.3%) and 31(23.3%), respectively. The highest incidences were observed in females under 20 years (47.3%) and males under 10 years (53.7%). The most frequent clinical sign was jaundice in 95.7% of patients. Deficient sanitary conditions and hygiene habits seemed to be the main risk factors in spreading HAV infection. Resumen: La infección por el virus de la hepatitis A (VHA) sigue siendo un problema de salud pública en los países en vías de desarrollo. El objetivo de la presente investigación fue determinar la incidencia de la infección por el VHA en individuos de la ciudad de Maracaibo, estado Zulia, Venezuela. Durante el periodo comprendido entre enero 2004 a diciembre 2007 se seleccionaron 1056 pacientes en edades de 1 a 60 años de ambos sexos (media ± DS: 27,48 ± 5,24), procedentes de los municipio Maracaibo y San Francisco ubicados en la ciudad de Maracaibo estado Zulia, Venezuela. La presencia de anticuerpos anti-IgM contra el virus de la hepatitis A se determinó mediante métodos convencionales de micro partículas enzimoinmunoanalisis (MEIA). Los resultados encontrados indican una seropositividad en 73 (35,1%), 76 (28%), 66 (24,3%), 35 (20,3%) individuos de las zonas Norte, Sur, Este, Oeste respectivamente, correspondientes al municipio Maracaibo y 31 (23,3%) ...